Traité de bave et d'éternité - Achard, Marcel 1899-1974; Barrault, Jean-Louis 1910-1994; Brunoy, Blanchette 1915-2005 (Re:Voir Video, 2008)
Founder in 1945 of the Letterist movement, precursor to Situationism, Fluxus, conceptual art and the happening, Isidore Isou invented the "discrepant", "chiseled" cinema in his key film On Venom and Eternity. The film created a scandal in Cannes in 1951 (the Lettrists arrived uninvited but Cocteau awarded it the avant-garde prize and later designed the poster), and heralded a new approach to avant-garde film
F 1951
Keywords: DVD-Video